Financial impact of Indonesia’s standardized inpatient class policy on hospital performance: A systematic review - Riska Rosita; Antin Okfitasari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Indonesia’s National Health Insurance system has introduced the Standardized Inpatient Class policy to reduce service disparities and improve equity and quality of inpatient care. However, compliance with standardized inpatient requirements entails substantial infrastructure and operational costs that may affect hospital financial performance. Purpose: To systematically examine how the implementation of the Standardized Inpatient Class policy influences hospital financial performance in Indonesia. Method: A systematic literature review was conducted following the PRISMA 2020 guidelines. Articles published between 2014 and 2025 were identified from Scopus, PubMed, and Google Scholar using predefined keywords related to standardized inpatient care, health financing, and hospital performance. Quality appraisal was conducted using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Eligible studies were screened using inclusion and exclusion criteria and synthesized using narrative thematic analysis. Results: Twelve studies met the inclusion criteria. The findings indicate that Standardized Inpatient Class implementation increases capital investment and operational costs, reduces bed capacity in some hospitals, and creates mismatches between reimbursement rates and actual service costs. Financial impacts vary by hospital ownership and location, with public and rural hospitals experiencing greater financial strain. Conclusion: While the Standardized Inpatient Class policy promotes equity and service quality, its implementation poses significant financial challenges for hospitals. Policy refinement, reimbursement adjustment, and targeted financial support are essential to ensure hospital financial sustainability.